Global trends in Alzheimer’s disease and other dementias in adults aged 55 and above (1992–2021): An age-period-cohort analysis based on the GBD 2021 - Qianqian Zhang; Yanwen Deng; Mo Xue; Zihan Ni; Guangyan Luo; Kan Tian (PLoS ONE, 2025)
Background Alzheimer’s disease and other dementias (ADOD) are growing global health challenges. While existing studies primarily focus on dementia prevention and management in individuals aged 65 and older, evidence suggests that cognitive decline and pathological changes begin earlier (≥55 years). This study focuses on this younger group to enable earlier risk identification and preventive interventions. Methods This study used GBD 2021 data to extract incidence, prevalence, mortality, and DALYs related to ADOD. Trends from 1992 to 2021 were assessed using the Age-Period-Cohort (APC) model. Future burden from 2022 to 2046 was projected with the Nordpred model and validated using the Bayesian Age-Period-Cohort (BAPC) model. Results From 1992 to 2021, ADOD incidence among individuals aged ≥55 increased by 143.88%. The age-standardized prevalence rate (ASPR) rose from 3,870.6 to 3,975.8 per 100,000. Deaths in 2021 were 1.75 times higher than in 1992. The age-standardized DALY rate was consistently higher in females, while males showed an upward trend (net drift, 0.05). APC analysis revealed the steepest incidence increase in the 60–64 age group, with earlier rises in males. Period effects indicated unfavorable incidence trends in high-middle SDI and middle-SDI regions, and similarly adverse mortality trends in high-middle and low-middle SDI regions. Projections suggest a slight increase in ASIR and ASMR by 2046, with females maintaining higher rates than males. Conclusion The global burden of ADOD among individuals aged 55 years and above remains substantial, particularly in East Asia and among females. Given regional heterogeneity, this study recommends developing and implementing region-specific interventions for more effective improvements.